The Decline in Generation Z Marriage Rates: Ma’ālāt Al-Af’āl Perspective - Ahmad Muflihul Wafa; Muhammad Harfin Zuhdi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
As a religion that is rahmatan lil 'alamin, Islam has determined that the only way to legally fulfill a person's biological needs is through marriage. Based on data from the Central Statistics Agency in 2024, the marriage rate in Indonesia is decreasing. Marriage in this decade is theoretically a generation, Gen Z is the ideal generation to get married. However, based on BPS data, Gen Z is actually postponing marriage. The reasons for Gen Z vary from factors of Globalization, Covid-19, to the shadow of divorce. The study used qualitative methods to explore the causes of marriage postponement by Gen Z. Maalaatul afal comes as a paradigm of legal instruments to assess marriage postponement. Postponement of marriage is permitted in maalaatul afal when it has reasons that are justified according to sharia.